2014
DOI: 10.4103/2230-8598.127164
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of enrolment and experiences of Rashtriya Swasthya Bima Yojana (RSBY) beneficiaries in Udupi district, India

Abstract: Background: Morbidities have emerged as major threats to livelihoods of the poor. An estimated 150 million have been reported as spending more than 40% of their income on their health needs. Aim: To identify the determinants of enrolment and experiences of Rashtriya Swasthya Bima Yojana (RSBY) benefi ciaries in Udupi district, India. Materials and Methods: A cross-sectional study was carried out in Udupi district between March and August 2012. A mixed method approach using qualitative and quantitative methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…14,15 However, only a limited number of studies in Asia have explored these factors at household level. 16,17 Given a unique socio-economic context, health system status and a unique family-based insurance modality of the NHIP, the factors established at those countries are likely to vary in the Nepalese context. Nonetheless, the evidence base for health insurance programs in Nepal remains very weak.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, only a limited number of studies in Asia have explored these factors at household level. 16,17 Given a unique socio-economic context, health system status and a unique family-based insurance modality of the NHIP, the factors established at those countries are likely to vary in the Nepalese context. Nonetheless, the evidence base for health insurance programs in Nepal remains very weak.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Udupi district of Karnataka state has, for example, shown that the majority of RSBY subscribers have found the scheme beneficial and were willing to renew their enrolment (Kamath et al 2014). Studies also show that in the large majority of the states, monthly healthcare expenditure for inpatient treatment has either reduced or remained constant since the introduction of the scheme (Sinha and Chatterjee 2014).…”
mentioning
confidence: 99%
“…The household head's characteristics [28] and the occupation of its members [27] are also known to be linked with the usage of the HI. More recent literature has confirmed the relevance of these variables in predicting the HI enrollment [8,10,13,29]. Among the states, we use Karnataka as the baseline, reference state.…”
Section: Explanatory Variablesmentioning
confidence: 99%